2022
DOI: 10.1108/k-06-2022-0842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of workplace bullying on knowledge hiding: The mediating role of emotional exhaustion and moderating role of workplace friendship

Abstract: PurposeWorkplace bullying has become a major challenge across the globe as it is associated with negative outcomes. Therefore, this study was designed to assess the impact of workplace bullying on knowledge hiding through emotional exhaustion. The study further investigated the moderating role of workplace friendship to reduce the detrimental effect of workplace bullying on knowledge hiding.Design/methodology/approachThe study collected data from 358 nurses working in three large cities (Karachi, Islamabad and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…spinning around them (Yu et al, 2021;Nawaz et al, 2022). Several research studies on healthcare employees over the previous year have found a rise in depression, anxiety, mental health disorders, psychological discomfort (Islam and Chaudhary, 2022;Lenzo et al, 2021), as well as employee well-being. Researchers and practitioners have recognized that poor well-being leads to less productivity, low job quality and poor decision-making (Ponting, 2020).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…spinning around them (Yu et al, 2021;Nawaz et al, 2022). Several research studies on healthcare employees over the previous year have found a rise in depression, anxiety, mental health disorders, psychological discomfort (Islam and Chaudhary, 2022;Lenzo et al, 2021), as well as employee well-being. Researchers and practitioners have recognized that poor well-being leads to less productivity, low job quality and poor decision-making (Ponting, 2020).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Workplace bullying by colleagues or leadership creates a harmful and health-threatening environment that negatively affects the physical and mental health of the individual (s) targeted (Chaudhary & Islam, 2022;Green, 2019a). Workplace absenteeism is a complication of workplace bullying related to stress levels affecting the health and well-being of the victim.…”
Section: Concepts Of Territorialism and Groupthinkmentioning
confidence: 99%
“…The COR theory of Hobfoll (1989) is a well-known theoretical framework that clarifies the significance of resources in influencing people's psychological and behavioral outcomes at work. This theory is based on the concept that individuals want to acquire and protect resources (Chaudhary and Islam, 2022;Islam and Chaudhary, 2022). It proposes that individuals are negatively affected when there is a likelihood of losing a resource, actual resource loss or a lack of anticipated resource gain; conversely, they are positively influenced when there is expected or actual resource gain (Hobfoll et al, 2018;Ahmad et al, 2023).…”
Section: Literature Review and Hypotheses Development Theoretical Fra...mentioning
confidence: 99%